Comparison of Mechanical Axis and Dynamic Range Assessed with Weight Bearing Radiographs and Navigation System in Closed Wedge High Tibial Osteotomy - Bae, Dae Kyung (Knee Surg Relat Res, 2017)
PURPOSE: To compare navigation and weight bearing radiographic measurements of mechanical axis (MA) before and after closed wedge high tibial osteotomy (HTO) and to evaluate post-osteotomy changes in MA assessed during application of external varus or valgus force. MATERIALS AND METHODS: Data from 30 consecutive patients (30 knees) who underwent computer-assisted closed-wedge HTO were prospectively analyzed. Pre- and postoperative weight bearing radiographic evaluation of MA was performed. Under navigation guidance, pre- and post-osteotomy MA values were measured in an unloaded position. Any change in the post-osteotomy MA in response to external varus or valgus force, which was named as dynamic range, was evaluated with the navigation system. The navigation and weight bearing radiographic measurements were compared. RESULTS: Although there was a positive correlation between navigation and radiographic measurements, the reliability of navigation measurements of coronal alignment was reduced after osteotomy and wedge closing. The mean post-osteotomy MA value measured with the navigation was 3.5°±0.8° valgus in an unloaded position. It was 1.3°±0.8° valgus under varus force and 5.8°±1.1° valgus under valgus force. The average dynamic range was >±2°. CONCLUSIONS: Potential differences between the postoperative MAs assessed by weight bearing radiographs and the navigation system in unloaded position should be considered during computer-assisted closed wedge HTO. Care should be taken to keep the dynamic range within the permissible range of alignment goal in HTO.